ELECTRICAL INSTALLATION AND POWER SAVING HOUSEHOLD - Mufid, Zainul; Musafa, Musafa (PT. Altin Riset Publishing, 2024)
This research aims to analyze compliance with the implementation of POJK 51 of 2017 This study aims to analyze the practices of electrical installation and energy-saving strategies in households. The research method used is a literature review involving the analysis of various literature sources and related research. The study found that improper electrical installation practices can increase the risk of fire and electrical disturbances. The use of energy-efficient labeled electrical appliances and smart home technology has been proven effective in reducing energy consumption in households. Factors such as public awareness of the importance of energy efficiency and the availability of information on energy-saving technologies also influence consumer behavior in choosing electrical appliances and managing energy use in households. Understanding these findings is expected to produce useful recommendations for researchers and practitioners in efforts to improve energy efficiency and electrical installation safety in households.